The differential effects of endogenous cathepsin and microorganisms on changes in the texture and flavor substances of grouper (Epinephelus coioides) fillets. Issue 18 (13th March 2020) - Zhang, Xicai; Xie, Jing
Abstract : This study reveals the different effects of endogenous proteases and microorganisms on the texture and flavor of grouper muscles. Abstract : Grouper is an important seafood species in China and has high economic value. However, the edible value of grouper is seriously affected by deterioration in the texture and flavor during refrigeration. The purpose of this study was to investigate the effects of endogenous cathepsin and microorganisms on texture softening and flavor changes in refrigerated grouper fillets. Iodoacetic acid and ProClin 300 were used to inhibit endogenous protease activity and microbial growth separately. Iodoacetic acid can inhibit the activity of cathepsin B, L, and calpain. Moreover, iodoacetic acid does not significantly affect the growth of microorganisms. The total amounts of bacteria and Pseudomonas spp. in the samples treated with ProClin 300 were less than 2 log CFU g −1 and 1 log CFU g −1 on the 18th day, and the activity of protease was not significantly affected. On the 6th day, the hardness of the iodoacetic acid treatment group decreased by 8%, while the ProClin 300 treatment group decreased by 28%, and changes in the free amino acids and volatile substances significantly exceeded those of the iodoacetic acid treatment group, indicating that endogenous protease was the main factor in the texture deterioration. A first-order exponential decay model indicated that cathepsin L was the most important protease for reducing the hardness of grouper fillets, and changes in the content of free amino acids and volatile substances indicated that microorganisms played a more important role in the deterioration of flavor substances compared to that played by endogenous protease.